Performance of crossbred gilts under the influence of age and body weight - NASKAR, S; DAS, ANUBRATA; BUJARBARUAH, K M; DAS, S K (The Indian Journal of Animal Sciences, 2014)
The influence of age and body weight at conception on productive and reproductive performance of crossbred gilt(87.5% Hampshire inheritance crossbred with Khasi local pig) was studied. Crossbred gilts (10), 4-5 months old. were taken and reared under general feeding, housing and management condition. Following productive and reproductive parameters of different parities were recorded - age at puberty (AP), age at first conception (AFC), age at first furrowing (AAF), weight at puberty and conception (kg), gestation period (days), inter-furrowing intervals (days), conception rate (%), litter size at birth (LSB). litter size' at weaning (LSW), litter weight at birth (LWB), hUer weight at weaning (LWW), individual litter weight at birth and weaning (kg). Mean age and weight at puberty and inter-furrowing interval (days) did not differ significantly but mean age and weight at conception and age at first furrowing differed significanlly between 2 groups. Whereas, the mean litter characteristics of 2 groups of animals under different parities did not vary significantly.Â  So, it was possible to produce more or same number ofweaners more efficiently than by mating gilt at early age rather than conventional weight and stage of sexual maturity. It also did not adversely affect the subsequent furrowing.